1976
DOI: 10.1111/j.1365-2125.1976.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect on blood pressure of beta‐adrenoceptor blocking drugs administered once daily and their duration of action when therapy is ceased.

Abstract: 1 The control of blood pressure achieved was similar whether pindolol or propranolol was given once or three times daily. 2 When the drugs were ceased the antihypertensive effect lasted for longer than 24 h. There was no rebound hypertension. 3 The full effect of the drug on blood pressure was seen within 24 h of its recommencement. 4 Changes in blood pressure, pulse rate, and plasma renin activity occurred but these were not considered to be causally related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…When it was given on a once daily basis the blood pressure remained as well controlled at the time of assessment as on twice daily treatment. The ability to control blood pressure on once daily treatment has been suggested with a number of 0-adrenoceptor blockers; propranolol and pindolol (Wilson, Morgan & Morgan, 1976), atenolol (Wilcox & Mitchell, 1977) and sotolol (Gabriel, 1977). Although as in the majority of the above trials the blood pressure was measured only once in the day in each phase, it seems reasonable to expect that the pressures at 24 h post dose on once daily treatment would reflect minimum control.…”
Section: Discussionmentioning
confidence: 99%
“…When it was given on a once daily basis the blood pressure remained as well controlled at the time of assessment as on twice daily treatment. The ability to control blood pressure on once daily treatment has been suggested with a number of 0-adrenoceptor blockers; propranolol and pindolol (Wilson, Morgan & Morgan, 1976), atenolol (Wilcox & Mitchell, 1977) and sotolol (Gabriel, 1977). Although as in the majority of the above trials the blood pressure was measured only once in the day in each phase, it seems reasonable to expect that the pressures at 24 h post dose on once daily treatment would reflect minimum control.…”
Section: Discussionmentioning
confidence: 99%
“…As the beneficial effects of propranolol in angina pectoris and cardiac arrhythmias result from blockade of cardiac f3-adrenoceptors (Shanks, 1976) Studies have already shown that once daily administration of conventional propranolol is effective in controlling raised arterial pressure throughout a 24 h period (Wilson et al, 1976;Douglas-Jones et al, 1978). However it has been suggested that use of this formulation may be associated with a higher incidence of adverse effects (Ross and Baber-quoted by Douglas-Jones et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Although observations in patients with hypertension have shown that satisfactory control of arterial pressure can be obtained throughout a 24 h period with twice daily administration (Berglund, Anderson, Habssen & Olander, 1973) and even once daily administration of propranolol (Wilson, Morgan & Morgan, 1976;Douglas-Jones, Baber & Lee, 1978), this may not be an effective regime for other 0306-5251/80/010033-08 $01.00 conditions such as angina or cardiac arrhythmias where the therapeutic effect may be more directly related to cardiac JJ-adrenoceptor blockade which is not maintained over 24 h after single dose of 100 mg propranolol (Aellig, 1976). Although a therapeutic effect with propranolol may be obtained in hypertension by giving the total daily amount as a single dose once per day, high plasma levels will occur shortly after administration which may produce adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Attention has been paid recently to the administration of the total daily dose of f3-adrenoceptor blocking drugs as a single dose. The administration of propranolol as a single dose each 24 h has been shown to control arterial pressure throughout this period (Wilson, Morgan & Morgan, 1976;Douglas-Jones, Baber & Lee, 1978) but at the end of the dose interval, the degree of cardiac /8-adrenergic receptor blockade will probably be small (Leahey et al, 1980a).…”
Section: Discussionmentioning
confidence: 99%